Epidural Needle Extension through the Ligamentum Flavum Using the Standard versus the CompuFlo®-Assisted Loss of Resistance to Saline Technique: A Simulation Study - E. Capogna; A. Coccoluto; M. Velardo (Anesthesiology Research and Practice)
Background. The CompuFlo® epidural system has been recently introduced and validated as an objective and sensible tool to detect the epidural space. We aimed to verify whether the high sensitivity of the instrument may help the anesthesiologist to identify the epidural space very early, limiting the extension of the Tuohy needle into the epidural space. Methods. In this prospective, simulation study, we evaluated the Tuohy needle extension through a simulated ligamentum flavum during the epidural procedure performed by 52 expert anesthesiologists by using the CompuFlo® epidural instrument or their standard loss of resistance to saline technique (LORT). Results. The mean (SD) needle extension length was 3.90 (3.71) mm in the standard technique group and 0.68 (0.46) mm in the CompuFlo® group (P<000001). The extremely reduced variability of the data in the CompuFlo® group (F test 0.01) made the results obtained with this instrument highly predictable. Conclusions. Puncturing high-resistance material that simulated the ligamentum flavum, the use of CompuFlo® has determined the arrest of the needle more precociously when compared with the traditional LORT.